Exploring the long-term impact of COVID-19: incidence and factors associated with insomnia in recovered patients - Phal, Nidhi Bharat; Savith, Akshatha; Meah, Ameena (International Journal of Research in Medical Sciences, 2023)
Background: COVID-19’s recognition as a multi-organ disease with diverse manifestations extends beyond acute illness into post-recovery phases. Post-COVID-19 infection, individuals often endure a spectrum of psychiatric symptoms, notably including persistent insomnia. This study aimed to investigate insomnia’s correlation with age, gender, comorbidity, infection severity, and biomarkers during hospitalization. Methods: This study employed a prospective design to explore the correlation between insomnia and various factors in COVID-19 survivors. Data were collected over a one-year period, with an emphasis on age, gender, comorbidity, infection severity, and biomarkers. Results: The incidence of insomnia among patients was approximately 7%. Notably, no significant statistical correlation emerged between insomnia and COVID-19 infection severity. Furthermore, insomnia prevalence remained unaffected by demographic factors such as gender, age, or comorbidity. Conclusions: The lasting impact of COVID-19 on mental health, particularly in terms of persistent insomnia, underscores the necessity for targeted interventions. Identifying factors contributing to insomnia among survivors holds paramount importance for developing effective management strategies that bolster overall well-being and quality of life. Recognizing and addressing insomnia as a significant long-term consequence of COVID-19 becomes imperative, as implementing appropriate interventions and support services can mitigate detrimental effects on mental and physical health. Ultimately, this contributes to improved outcomes and an enhanced quality of life for survivors.